The Role of Parenting in Improving Maternal Health Literature Against Stunting in District Pati - Hartuti Hartuti; Haryono Haryono; Rusdarti Rusdarti; Yuli Kurniawati Sugiyo Pranoto (International Conference on Science, Education, and Technology, 2021)
Health literacy for mothers is very important regarding nutrition and child health, given the stunting problem that befell children in Indonesia. The cause of elevating the problem of stunting, especially in Pati is the low maternal knowledge in terms of parenting (caring, educating, guiding). This study aims to: (1) determine the problems of parenting education activities in order to increase maternal knowledge related to nutritional status during pregnancy, and (2) determine the supporting and inhibiting factors in parenting education activities. This research used a mixed method with interview, documentation, observation, and test techniques that will be analyzed qualitatively and quantitatively. The results of data analysis showed that parenting education activities to question stunting were declared effective in t-test calculations so that they were considered significant among young mothers' knowledge before and after participating in parenting education.